2019
DOI: 10.1093/zoolinnean/zlz134
|View full text |Cite
|
Sign up to set email alerts
|

Biomes, geology and past climate drive speciation of laminate-toothed rats on South African mountains (Murinae: Otomys)

Abstract: Mitochondrial DNA sequences (1137 bp) of the cytochrome b gene and craniodental and craniometric data were used to investigate the evolutionary relationships of six putative rodent taxa of Otomys (family Muridae: subfamily Murinae: tribe Otomyini) co-occurring in the Western Cape and Eastern Cape provinces of South Africa. Phylogenetic analysis of 20 new sequences together with craniodental and craniometric characters of 94 adult skulls reveal the existence of a unique lineage of Otomys cf. karoensis (named he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 34 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…1 The exact number of extant Otomys species is contentious and a number of cryptic species have been identified, while others await further elucidation. [2][3][4][5] Some studies suggest that speciation has occurred along biomes, with phenotypic and genotypic divergent lineages corresponding to the Fynbos/Albany Thicket and Grassland biomes in the case of Otomys irroratus and Otomys karoensis. 2,3 Geometric morphometric analyses carried out on the crania of Otomys unisulcatus also failed to support the genetic groupings, but rather followed biome boundaries, indicating previous environmental adaptations.…”
Section: Taxonomy and Phylogeny Of Otomys Sloggettimentioning
confidence: 99%
See 2 more Smart Citations
“…1 The exact number of extant Otomys species is contentious and a number of cryptic species have been identified, while others await further elucidation. [2][3][4][5] Some studies suggest that speciation has occurred along biomes, with phenotypic and genotypic divergent lineages corresponding to the Fynbos/Albany Thicket and Grassland biomes in the case of Otomys irroratus and Otomys karoensis. 2,3 Geometric morphometric analyses carried out on the crania of Otomys unisulcatus also failed to support the genetic groupings, but rather followed biome boundaries, indicating previous environmental adaptations.…”
Section: Taxonomy and Phylogeny Of Otomys Sloggettimentioning
confidence: 99%
“…[2][3][4][5] Some studies suggest that speciation has occurred along biomes, with phenotypic and genotypic divergent lineages corresponding to the Fynbos/Albany Thicket and Grassland biomes in the case of Otomys irroratus and Otomys karoensis. 2,3 Geometric morphometric analyses carried out on the crania of Otomys unisulcatus also failed to support the genetic groupings, but rather followed biome boundaries, indicating previous environmental adaptations. 6 This, together with the adaptability observed in fossil Otomys communities when faced with environmental and climatic change on the south coast of South Africa 7 , as well as the fact that up to three or more Otomys species may live sympatrically in an area 1,2,7 , indicates the flexibility and plasticity of this murid subfamily.…”
Section: Taxonomy and Phylogeny Of Otomys Sloggettimentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptic speciation amongst the laminate toothed rats (family Muridae: subfamily Murinae: tribe Otomyini), to which the vlei (Otomys irroratus), bush Karoo (O. unisulcatus) and Sloggett's ice rat (O. sloggetti) belong, is common, especially in mountainous habitats (Taylor et al 2019). In fact, recent taxonomic work has demonstrated that O. irroratus senso lato can be confused morphologically with at least one other cooccurring species O. karoensis (Taylor et al 2019). As such, I recommend that the specific assignment of the three laminate toothed rats putatively present in MZNP be verified through the collection of specimens for morphological and genetic analyses.…”
Section: Taxonomic Conundrums and Future Research Prioritiesmentioning
confidence: 99%
“…the introduction of passive infra-red camera traps) are likely to have improved the detectability of some species that other more traditional techniques failed to detect in the past (De Bondi et al 2010). Moreover, the nomenclature (and, effectively, the number) of individual mammal species may change over time as new knowledge about the evolutionary history of a species or group of species becomes available and they are either divided or synonymised (Taylor et al 2019). Thus, the aims of this study were to provide an historical review of the mammal species of the MZNP and to update the mammal checklist for the park.…”
Section: Introductionmentioning
confidence: 99%